POLITIK HUKUM PENGATURAN SISTEM INFORMASI PEMILU - Nurush Shobahah; Much Anam Rifai (Legacy: Jurnal Hukum dan Perundang-Undangan, 2021)
The Election information system is a one of tool used by General Election Commissions (KPU) to wage The Election in order to maintenance transparency, effectiveness and accountability. It has been done since 2014. However, there has been a few problem using these instruments, especially in use of Sipol, in absensce of its mandatory regulation. Through this normative legal research, researchers are trying to analyze tthe basics of legal policy of the Election Information System regulation, and also to analyze the differenciation between the purpose in using Election Information System Regulation from The Regulation Maker and General Election Commissions (KPU). In facts, most of Electoral Information System used by KPU are categorized as unmandatory regulation which is has no legal basis or legal mandatory regulation. This cause a problem such as a resistance from public for the subjectivity or will from the regulation maker in legalizing this electoral information system. Since 2019 National Election, th regulation maker still mandate that election conducted in conventional way or a manual system despite the will from KPU to use those electoral information system in order to maintenance transparency, effectiveness and accountability.